Les pratiques coutumières de gestion des ressources naturelles dans le contexte de la mondialisation économique : cas de l’arganeraie marocaine - Hassan Faouzi (Études Caribéennes)
For centuries, in the Moroccan arganeraies, the rural populations organized the control of the space on which people depended for their livelihood by adopting practices of traditional management. But, recently, in the context of the economic globalization and fuelled by strong demand for the argan oil, we are experiencing for a great pressure exercised on natural resources of the arganeraie, which exacerbates the usage conflicts and contributes to the degradation of this ecosystem, which reflecting the inadequacy of these traditional management systems to this new context.